2020
DOI: 10.1103/physrevlett.124.045101
|View full text |Cite
|
Sign up to set email alerts
|

Electron Heating by Debye-Scale Turbulence in Guide-Field Reconnection

Abstract: We report electrostatic Debye-scale turbulence developing within the diffusion region of asymmetric magnetopause reconnection with moderate guide field using observations by the Magnetospheric Multiscale (MMS) mission. We show that Buneman waves and beam modes cause efficient and fast thermalization of the reconnection electron jet by irreversible phase mixing, during which the jet kinetic energy is transferred into thermal energy. Our results show that the reconnection diffusion region in the presence of a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 37 publications
7
60
0
Order By: Relevance
“…Such distributions can be unstable to both quasi-parallel and oblique whistlers at the same time. This is supported by reported events where the quasi-parallel and oblique whistlers co-exist in the separatrix regions on the magnetospheric side of the magnetopause (Zhou et al, 2018;Khotyaintsev et al, 2019). Figure 7A summarizes different types of VDFs leading to whistler generation in the vicinity of the X-line.…”
Section: Whistlerssupporting
confidence: 66%
See 2 more Smart Citations
“…Such distributions can be unstable to both quasi-parallel and oblique whistlers at the same time. This is supported by reported events where the quasi-parallel and oblique whistlers co-exist in the separatrix regions on the magnetospheric side of the magnetopause (Zhou et al, 2018;Khotyaintsev et al, 2019). Figure 7A summarizes different types of VDFs leading to whistler generation in the vicinity of the X-line.…”
Section: Whistlerssupporting
confidence: 66%
“…Eventually, the electron two-stream instability would take over, leading to higher phase speeds and continuing to thermalize the beam. This scenario was recently confirmed in an event study of guide-field reconnection at the dayside magnetopause by MMS (Khotyaintsev et al, 2019); it was shown that the electron reconnection jet was gradually thermalized due to the waveparticle interaction of broadband electrostatic turbulence.…”
Section: Broadband E || Wavesmentioning
confidence: 64%
See 1 more Smart Citation
“…Turbulence and coherent structures universally exist in space plasmas. Kinetic-scale turbulence is strongly coupled to dissipative processes such as magnetic reconnection and shocks [46][47][48]. One form of turbulence in space plasmas is flow eddies.…”
Section: Scientific Objectivesmentioning
confidence: 99%
“…At the Earth's magnetopause, magnetic reconnection is generally asymmetric, and often with a guide field (e.g., Burch & Phan, ; Chen et al, ; Genestreti et al, ; Khotyaintsev et al, ; Webster et al, ; Zhou et al, ). The superposition of the positive/negative bipolar‐type Hall magnetic field and the guide field can enhance/reduce the out‐of‐plane magnetic field in the two different exhausts.…”
Section: Introductionmentioning
confidence: 99%